Mother's Knowledge About Dental Health With Carrying Events In Children In Public Elementary School 1 Saleppa, Banggae District - Al-Hijrah, Muh fauzar; Armidayanti, Armidayanti (Preventif : Jurnal Kesehatan Masyarakat, 2020)
Dental caries attacks all people, all ages, both men and women, all tribes, races and at all levels of social status. The World Health Organization (WHO) survey in 2013 said that as many as 87% of school-age children around the world and most adults had suffered from dental caries. According to the Basic Health Research (Riskesdas) in 2013, the prevalence of dental caries in children aged 5-9 years 28.9%, up from 2007 amounted to 21.6%. Dental and oral health services for elementary school children and the same level in Majene Regency were not optimally implemented in 2017 the percentage of students examined was 53.5% and those who received care were only 20% of the number that should be treated. This study aims to identify the relationship of maternal knowledge about dental health with caries incidence in children. This research uses observational research with cross sectional approach that connects independent variables with dependent variables at the same time. The total population in this study was 65 parents (mothers) students, and the sampling technique used was total sampling. Research Results From the Chi Squaredi test results obtained value ρ = 0,000 where the value of ρ is less than 0.05 which means there is a meaningful relationship between the knowledge of mother with caries incidence in children. It is suggested to mothers to seek more information about maintaining oral health and giving good food for dental health and it is hoped that the school will organize a School Dental Health Effort to pay more attention to the oral health of children